Isolation and Detection of Bacteriocin-Like Inhibitory Substances-Producing Bacteria from Fermented Mare’s Milk Sumbawa - Alifia Issabella Mulyawati; Tri Ardyati; Yoga Dwi Jatmiko (Jurnal Biodjati, 2019)
Bacteriocin-like inhibitory substances (BLIS) produced by bacteria is a promising future food preservative agent. This study aimed to obtain bacterial strains that can produce broad-spectrum antibacterial agents and identify the best BLIS producer species based on 16S rDNA sequences. The bacterial strains were isolated from fer-mented mare’s milk using MRS and M17 agar medium. The isolates then were initially screened based on its antibacterial activity of crude cells against Staphylococcus aureus ATCC 6538. The selected strains were cultured and harvested for its cell-free supernatant (CFS). The pH of CFS was adjusted to 6.5 then used for antibacterial activity as-says against ten pathogenic bacteria. Also, the proteinaceous nature of BLIS compound was confirmed by testing with proteinase K. The gDNA of selected isolates was extracted and the 16S rDNA was am-plified using the polymerase chain reaction method then sequenced. The 16S rDNA sequences of the selected strains were used to identify the species using BLAST nucleotides from NCBI then the phylogenetic trees were constructed. 32 isolates was obtained, but only three iso-lates (BC9, SB7, and DC12) were selected as a result of antibacterial screening for further assays. The neutralized-CFS (N-CFS) of these isolates exhibited broad-spectrum antibacterial activity. The N-CFS could be assumed as BLIS. The isolate of BC9 was identified as Ba-cillus amyloliquefaciens strain BC9 that has 99.99 % similarity with B. amyloliquefaciens KC-1, SB7 was Lactobacillus plantarum strain SB7 that has 99.99 % similarity with Lb. plantarum JMC 1149T, and DC12 was Lactobacillus rhamnosus strain DC12 that has 100 % sim-ilarity with Lb. rhamnosus DSM 20021T. Thus, the BLIS produced by those strains is potential for future food and beverages preservations.